HUMAN CAPITAL STUDY: CAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR FOR BOOSTING JOB SATISFACTION? - Della Amaylia Ashari; Iwan Hermawan; Inayah - (BISECER (Business Economic Entrepreneurship), 2023)
Organizational Citizenship Behavior (OCB) is a challenge in the world of work today, because organizations will certainly feel happy if they have employees who behave OCB. Organizations need to pay attention to employees and be able to manage employees so that they have superior employees that are not owned by other organizations. In this case it will also be beneficial for the organization. Problems that occur in organizations related to work ethics such as discipline. Therefore, it is necessary to build an OCB model that impacts Job Satisfaction in the workplace. In order to solve these organizational problems, it can facilitate the emergence of a work ethic. This research is a quantitative study, with a sample of 138 respondents from PT Pertamina Lubricants – Production Unit Cilacap. Multiple linear regression analysis instruments and data processed using SPSS. The empirical test results prove that the dimensions of OCB including altruism, awareness, politeness, sportsmanship, and the virtues of citizenship have a significant effect on job satisfaction. The contribution of this study uses the perspective of human capital theory with managerial implicit which emphasizes the importance of building an adaptive work environment, building a better colletivism culture and increasing spirituality in the workplace.